"""M"" is for malice /" - "Grafton, Sue." (New York)
"""A Marian Wood book."""
Keywords: "MILLHONE, KINSEY (FICTITIOUS CHARACTER) --;FICTION.;WOMEN PRIVATE INVESTIGATORS -- CALIFORNIA --;CALIFORNIA -- FICTION.;DETECTIVE AND MYSTERY STORIES. GSAFD"